A treatise on the preparation and delivery of sermons - Broadus, John Albert, 1827-1895 (Southern Baptist classic reprint., 2005)
This is the classic "Dargan Edition" of John A. Broadus' masterful treatise on "The Preparation and Delivery of Sermons" updated in 1897 by his colleague, Edwin Charles Dargan. Originally written in 1870, this book became the standard text-book for more than a generation, passing through 22 editions in the US alone. It was used as a text in the United Kingdom, Japan, China and Brazil in the 19th century. It has been updated twice in the 20th century, but these updates, in many ways, were unfaithful to Broadus' original work. There is nothing like "The Dargan Edition" of Broadus. - Publisher.